Quality Nutrient Identification in Liquid Organic Fertilizer (Goat Urine and Banana Stumps) and Its Application on Growth of Chili (Capsicum frutescens) - Aldy Bahaduri Indraloka; Mohamad Ilham Hilal; Abdus Salam Junaedi (International Journal of Science and Environment (IJSE), 2025)
Agricultural waste such as goat manure and urine could be a source of environmental pollution and a source of disease if it can’t be processed into beneficial fertilizer. The use of organic fertilizers could increase plant growth and can prevent land quality degradation, but some of the weaknesses in the application of organic fertilizer are the lack of information on nutrient content and its effects on plant growth. The aim of this research is to analyse the fermentation periods for producing the highest macro nutrient in liquid organic fertilizer made from goat urine and banana stumps. The results showed that the effect of the fermentation periods gave different results of macro nutrients. The recommendation for fermentation periods required to produce the highest macro nutrient content was P2 (21 days), the percentage value of nutrients in (P2: 21 days) were Nitrogen (1.83%), Phosphorus (0.56%) and Potassium (1.20%). The research results also showed that the P4 treatment (20 mL of liquid organic fertilizer) giving the highest value on several parameters in chili (height, number of leaves, fresh weight, root length, number of flower and fruits). P1 and P3 recommended for appearance of flowers (30 DAT) and P4 recommended for stimulating fruit primordia.